The Need for Robust Critique of Arts and Health Research: Young People, Art Therapy and Mental Health - Grebosz-Haring, Katarzyna; Thun-Hohenstein, Leonhard; Schuchter-Wiegand, Anna Katharina; Irons, Yoon; Bathke, Arne; Phillips, Kate; Clift, Stephen (Frontiers in Psychology, 2022)
We describe work in progress to conduct a systematic review of research on effects of arts-based programs for mental health in young people. We are at the stage of searching for relevant studies through major databases and screening extant systematic reviews for additional research which meet our inclusion criteria. At this stage, however, concerns have arisen regarding both the quality of existing primary studies and of recently published systematic reviews in this area of arts and health. As a case in point, in this paper we focus on one research report on art therapy with adolescent girls (Bazargan and Pakdaman, 2016) and its inclusion in three systematic reviews (Ponomarenko et al., 2017; Cohen-Yatziv and Regev, 2019; Bosgraf et al., 2020). We demonstrate that the reviews fail to undertake a robust critique of the Bazargan and Pakdaman paper, and that the paper and reviews are flawed. Drawing on recent criticisms of systematic reviewing (Ioannidis, 2016; Hammersley, 2020), we consider the value of proceeding with our systematic review as initially planned.